4
$\begingroup$

I need to somehow show that $$\cos(x)+\cos(3x)+...\cos\left((2n-1)\,x\right)=\frac{\sin(2nx)}{2\sin(x)}$$ for some integer $n>0$.

This seems impossible to me since if I consider the left-hand side, I don't know any identity of the form $\cos(ax)+\cos(bx)$. So, I can’t do anything. On the other hand, if I consider the right-hand side, the only identity I know is $\sin(2nx)=2\sin(nx)\cos(nx)$, which doesn’t seem to help me. Finally, Taylor expansion is not helpful either.

How can I show this?

$\endgroup$
  • 1
    $\begingroup$ The identities to add trigonometric functions are very useful. Here they are. $\endgroup$ – OR. Mar 26 '14 at 21:57
  • $\begingroup$ My first thought is perhaps multiply by $sin(x)$, which would give terms on the left as $cos(nx)sin(x)$ which looks like part of a sine angle addition formula. $sin(a + b) = sin(a)cos(b) + sin(a)cos(b)$ Then you can look at $sin(a - b) = sin(a)cos(b) - sin(b)cos(a)$. Finally, you could write $sin(a)cos(b) = \frac{sin(a + b) + sin(a - b)}{2}$ which gives terms like this: $cos\left((2n - 1)x\right)sin(x) = \frac{sin\left(x + (2n - 1)x\right) + sin\left(x - (2n - 1)x\right)}{2} = \frac{sin\left(2nx\right) + sin\left(2x(n - 1)\right)}{2}$. No idea if that will help though. $\endgroup$ – Jared Mar 26 '14 at 21:59
  • 1
    $\begingroup$ Have you worked with complex numbers? If you have then transforming the trigonometric functions into exponentials will solve this problem. $\endgroup$ – OR. Mar 26 '14 at 22:00
  • $\begingroup$ Equivalently you can do what Jared is saying. After you break up the products of cosines with the sine into sums, the whole sum will telescope. $\endgroup$ – OR. Mar 26 '14 at 22:03
  • $\begingroup$ I was searching for it, because this is a classical question, so it was likely to have been asked already. Here it is the computation. $\endgroup$ – OR. Mar 26 '14 at 22:07
1
$\begingroup$

Using the identity $e^{i\theta}+e^{-i\theta}=2\cos(\theta)$, you can express the sum of the cosine terms as:-

$\cos(x)+\cos(3x)+\cdots+\cos((2n-1)x)=\frac{1}{2}(\sum_{k=1}^ne^{j(2k-1)x}+\sum_{k=1}^ne^{-j(2k-1)x})$

The right hand side of the above equation is the sum of two Geometric progressions for the complex exponential terms, where

$$\sum_{k=1}^ne^{j(2k-1)x}=\frac{e^{jx}(1-(e^{j2x})^n)}{1-e^{j2x}}=\frac{e^{jx}-e^{j(2n+1)x}}{1-e^{j2x}}$$

$$\sum_{k=1}^ne^{-j(2k-1)x}=\frac{e^{-jx}(1-(e^{-j2x})^n)}{1-e^{-j2x}}=\frac{e^{-jx}-e^{-j(2n+1)x}}{1-e^{-j2x}}$$

This leads (after some algebraic manipulation) to

$\large \sum_{k=1}^ne^{j(2k-1)x}+\sum_{k=1}^ne^{-j(2k-1)x}=\frac{e^{j(2n-1)x}+e^{-j(2n-1)x}-(e^{j(2n+1)x}+e^{-j(2n+1)x})}{2-(e^{j2x}+e^{-j2x})}\\\large=\frac{2\cos((2n-1)x)-2\cos((2n+1)x)}{2(1-\cos(2x))}=\frac{\cos((2n-1)x)-\cos((2n+1)x)}{1-\cos(2x)}$

Using the sum of angles identities for trigonometry (as stated below)

$\cos(a+b)=\cos(a)\cos(b)-\sin(a)\sin(b)$

$\cos(a-b)=\cos(a)\cos(b)+\sin(a)\sin(b)$

$\cos(2a)=\cos^2(a)-\sin^2(a)=1-2\sin^2(a)$

we can further simplify the sum of the two Geometric progressions to

$$ \frac{\cos(2nx)\cos(x)+\sin(2nx)\sin(x)-\cos(2nx)\cos(x)+\sin(2nx)\sin(x)}{1-1+2\sin^2(x)}\\=\frac{2\sin(2nx)\sin(x)}{2\sin^2(x)}=\frac{\sin(2nx)}{\sin(x)}$$

Thus we have

$$ \frac{1}{2}(\sum_{k=1}^ne^{j(2k-1)x}+\sum_{k=1}^ne^{-j(2k-1)x})=\frac{\sin(2nx)}{2\sin(x)}$$

so that the sum of the Cosine terms evaluates as follows:-

$$\cos(x)+\cos(3x)+\cdots+\cos((2n-1)x)=\frac{\sin(2nx)}{2\sin(x)}$$

$\endgroup$
  • $\begingroup$ thanks for your response, really helpful $\endgroup$ – loukanikos Mar 27 '14 at 21:09
  • $\begingroup$ You are welcome, and I am glad to help. Although my proof is fairly long, I have tried to detail step by step how to proceed to the answer. $\endgroup$ – Alijah Ahmed Mar 27 '14 at 21:23
3
$\begingroup$

You can prove this by induction. Hints below.

Base case

For $n=1$, choose an appropriate trig identity to expand the numerator $\sin 2nx =\sin 2x$ on the right hand side.

Inductive case

Assume

$$\cos x + \cos 3x + \ldots + \cos ((2n-3)x) = \frac{\sin((2n-2)x)}{2\sin x}$$

This gives

\begin{align} \cos x + \cos 3x + \ldots + \cos ((2n-1)x) &= \frac{\sin((2n-2)x)}{2\sin x} + \cos ((2n-1)x) \\ &=\frac{\sin(2n-2)x + 2\cos ((2n-1)x) \sin x}{2\sin x} \\ &=\frac{\sin(2(n-1)x-x) + 2\cos ((2n-1)x) \sin x}{2\sin x} \end{align}

Then use a trig identity to expand $\sin(2(n-1)x-x)$, simplify and you should see fairly immediately that another trig identity gets you to $2\sin 2nx$ on the numerator.

$\endgroup$
  • $\begingroup$ thanks, that is much easier and less messy than using complex numbers $\endgroup$ – loukanikos Mar 27 '14 at 21:11
  • $\begingroup$ @it's a pleasure to help :). When I wrote my answer I guessed you probably wouldn't want complex numbers. But if you were fluent with complex numbers Weirdstress Function's answer would probably be a better way to go -- they tend to be easier than using traditional trig identities once you get used to them. $\endgroup$ – TooTone Mar 27 '14 at 21:56
1
$\begingroup$

Use Euler's identity $$ e^{ix}=\cos x + i \sin x $$ So your case can be written as the real part of \begin{align*} \cos x + \cos 3x + \cdots + \cos(2n-1)x +i(\sin x + \sin 3x + \cdots + \sin (2n-1)x ) &= \sum_{k=1}^n e^{i(2k-1)x}\\ &= e^{ix}\frac{e^{2nix}-1}{e^{2ix}-1}\\ &= \frac{\sin 2nx}{2\sin x} + i (\cdots) \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.